Direct displacement-based seismic design of flexible-base structures subjected to pulse-like ground motions - Lu, Yang; Hajirasouliha, Iman; Marshall, Alec M. (Elsevier, 2018)
In this paper, a practical displacement-based framework is presented for seismic design of flexible-base structures in near-fault regions. Particular attention is given to pulse-like motions that may cause significant damage to building structures. The proposed design methodology utilises displacement response spectra constructed using a new procedure, which takes into account the effect of pulse period. An equivalent fixed-base single-degree-of-freedom oscillator is adopted to capture the salient features of an actual soil-structure interaction (SSI) system in order to facilitate the design process. Two step-by-step direct-displacement based design (DDBD) procedures based on compatible inelastic spectra and equivalent linearisation are introduced. The effectiveness of the stated design procedures is examined using results of nonlinear response history analysis of two example SSI systems subjected to a set of sixteen spectrum-compatible near-fault pulse-like ground motions. The results of this study suggest that the procedure based on inelastic design spectra, in general, provides a better design solution than using an elastic linearisation method, especially when structures are designed with a higher ductility demand.